Multi-Software Platform for Solving of Multibody Systems Synthesis - Sapietova, Alzbeta; Saga, Milan; Novak, Pavol (Communications - Scientific letters of the University of Zilina, 2012)
The paper deals with design and application of multi-software platform for solving of mechanical multi-body system problems. The Adams working interface and open architecture of Matlab programming language enable share common data during parallel run of simulations. This process was used for design and implementation of evaluation algorithm and optimization of technical equipment parameters in terms of their mechanical properties. The goal is to present the mapping process of the working space of the chosen manipulating equipment and application of the optimizing approach to find its geometry parameters. Multi-software technique will be applied for computational realization i.e. Adams and Matlab.